Venture Capital in Central and Eastern Europe - Slovakian Case - Magdalena Markiewicz (Communications - Scientific letters of the University of Zilina, 2005)
Financing business at the very first stage or expanding it, together with active participation in creating strategies of management, marketing, sales and other fields, may be done by venture capital funds and venture investors. They offer capital, know-how, expertise and assistance and are ready to take significantly higher risk for the average period of 5-7 years. Venture investments are especially effective in stock-oriented markets, due to an opportunity of easy disinvestment through public offering, or in emerging markets, where they meet prospects of very high rates of return. Private equity and venture capital investments may highly support the development of knowledge and innovation, which are among the keys to economic growth and welfare. These investments, rising in Europe, support lowering the development gap between the US and the EU.